ACS-NSQIP - Surgical risk calculator accurately predicts outcomes of laparotomy in a prospective study at a tertiary hospital in Tanzania - Tryphone Buchwald Kagaruki; Nashivai Elias Kivuyo; Fransia Arda Mushi; Frank Domician Muhamba; Larry Onyango Akoko (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Introduction: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) surgical risk calculator is excellent in predicting postoperative complications. Validation in resource-limited settings and applicability in gastrointestinal surgery is still unclear. Objective: The study aimed to determine the accuracy of the ACS-NSQIP surgical risk calculator in predicting the 30days postoperative adverse outcomes among patients who underwent laparotomy. Methods: A Single hospital-based, prospective cohort study was done at Muhimbili National Hospital in Tanzania from April 2021 to December 2021 recruiting patients aged 18 and above who underwent primary laparotomy. SR calculator variables were obtained from patients and entered manually to categorize patients into low and high-risk. Patients were followed up for thirty days for the outcome. The predicted risk was compared with actual occurrence to obtain personal risk ratios. The c-statistics of > 0.7, Brier of score < 0.25 and Index of Prediction Accuracy score were used for discrimination, accuracy, and usefulness of the model respectively. Results: ACS -NSQIP SR-Calculator discriminated well the risks of cardiac complications, re-laparotomy, Anastomotic leak, and death (c-statistic > 0.7) Poor discrimination was observed for the length of hospital stay (c-statistics 0.518). However, SR-calculator shows high calibration potential for all complications with a Brier score < 0.25 (0.002 - 0.144) and an IPA score ranging from 0.225 - 0.969. Conclusion: The ACS -NSQIP SR-calculator accurately predicted postoperative outcomes for patients requiring laparotomy. SR-Calculator is a reliable tool for preoperative shared decision-making and counseling. The model should be adopted to strengthen the healthcare system in a low-income country. What is already known about this subject?➢ The ACS NSQIP surgical risk calculator is accurate in predicting the outcome of the Surgical procedure. ➢ ACS NSQIP surgical risk calculator was validated in the USA ➢ The SRC is associated with surgical care improvement whenever applied. What are the new findings? ➢ The SRC accurately predicted the 30-day outcomes associated with primary laparotomy except for the length of hospital stay, discharge for other services, and veno-thromboembolic events. ➢ The risk ratio (RR) provides a preliminary estimation of specific complications for a single patient. ➢ Index of prediction Accuracy (IPA) reliably summarizes the discrimination and calibration of the ACS-NSQIP-SR-Calculator. ➢ The SRC can be validated in a resource-limited setting and can be a source of surgical care improvement. How might these results affect future research or surgical practice? ➢ The results of this study will provide a comparison between our institution and other international situations where a calculator had been tested and surgical service improvement locally.